Pengaruh Penggunaan Perpustakaan Sekolah Sebagai Sumber Belajar Terhadap Prestasi Belajar Siswa Kelas VII Pada Bidang Studi IPS - Hizam, Ibnu; Zaetun (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This study aims to explore the effect of school libraries on learning achievement. The researcher is a quantitative research using statistical data analysis. The sample in this study amounted to 41 students who were taken randomly (random) from a total population of 209 students in class VII of SMP Negeri 4 Gerung. Based on the results of hypothesis testing which says that there is an effect of using library media on the learning achievement of seventh grade students at SMPN 4 Gerung by using the product moment correlation formula, it shows that student learning achievement can be improved through the implementation of the library which in the test obtained Rxy of 0.495 which is interpreted as still in a high significant level.